Cognitive Decision Strategies Adopted in Reminder Tasks by Trained Judges When Discriminating Aqueous Solutions Differing in the Concentration of Citric Acid. Issue 3 (15th April 2013) - Stocks, Miriam A.; van, Danielle; Hautus, Michael J.
Abstract Four sensory difference tests – A‐Not A, two‐alternative forced choice (2‐AFC) and their reminder counterparts, A‐Not A with reminder task (A‐Not AR) and 2‐AFC with reminder task (2‐AFCR) – were applied to pairs of aqueous solutions containing different concentrations of citric acid to determine the decision strategy adopted by judges in the reminder tasks, and which of the four tasks has the greatest test sensitivity. Three solution types, each containing a different number of compounds, were employed to determine if the strategy adopted or test sensitivity is contingent upon the number of compounds in solution. Auditory and visual research suggests that observers adopt a tau (τ) strategy for simple stimuli (which could be likened to a solution containing a few compounds) and a beta (β) strategy for complex stimuli (which could be likened to a solution containing several compounds). Results suggest that the strategy adopted for the 2‐AFCR task is fairly consistent across judges and solution types, whereas that for A‐Not AR is fairly consistent across judges but depends on solution type. All four tasks were found to have similar test sensitivity. The results highlight the need for caution when using difference tests when the decision strategy being used by judges is not known. Relatively large errors in estimates of performance can result from an incorrect assumption. Practical Applications Changes to ingredients, processing and storage methods frequently challenge manufacturers who strive to maintain products that will appeal to consumers. Difference tests can assist the manufacturer in determining the effect of such changes on perception. Difference tests need to be effective in use and must produce valid and reliable results. A‐Not A and 2‐AFC tasks are sensitive to sensory differences, and are frequently used, but require a time‐consuming familiarization procedure. A‐Not AR and 2‐AFCR do not require this, as they provide a comparative reminder stimulus on each trial. Comparisons of these four tasks showed all to be equal in test sensitivity, a component of validity, however, not equal in reliability. Of the reminder tasks, A‐Not AR was less reliable, as decision strategy depended on stimulus type, whereas in 2‐AFCR, decision strategy was more consistent, particularly for stimuli containing more components.